Gemcitabine and bendamustine is a safe and effective salvage regimen for patients with recurrent/refractory Hodgkin lymphoma: Results of a phase 1/2 study. Issue 6 (10th December 2019) - Cohen, Jonathon B.; Wei, Lai; Maddocks, Kami J.; Christian, Beth; Heffner, Leonard T.; Langston, Amelia A.; Lechowicz, Mary Jo; Porcu, Pierluigi; Flowers, Christopher R.; Devine, Steven M.; Blum, Kristie A.
Abstract : Background: Both gemcitabine and bendamustine have been evaluated in patients with recurrent/refractory Hodgkin lymphoma but to the authors' knowledge not as a doublet. The authors completed a phase 1/2 trial to identify the optimal dose and frequency of administration and to assess the efficacy of this combination in patients with recurrent/refractory Hodgkin lymphoma. Methods: Patients were treated up to a maximum dose of gemcitabine (1000 mg/m 2 on day 1) and bendamustine (120 mg/m 2 on days 1 and 2), which was determined to be the recommended phase 2 dose, administered every 21 days for up to 6 cycles. Patients could discontinue study therapy after 2 cycles to proceed with autologous or allogeneic stem cell transplantation. Results: No dose‐limiting toxicities were identified, but 4 patients experienced grade 3 to 5 pulmonary adverse events (toxicity was graded according to Common Terminology Criteria for Adverse Events [version 4]). A total of 26 patients were enrolled having completed a median of 4 prior lines of therapy (range, 1‐7 lines), including 13 patients at the recommended phase 2 dose, in whom the overall response rate was 69% and the complete response rate was 46%. The median progression‐free survival for the phase 2 patients was 11 months (95% CI, 3 months to not reached), and the median overall survival for this group had not been reached at the time of last follow‐up (95% CI, 4 months to not reached). Conclusions: This doublet was found to be tolerable and effective, but patients must be monitored closely for pulmonary toxicity. The authors currently are evaluating this doublet in combination with nivolumab. Abstract : Gemcitabine and bendamustine can be combined safely in patients with recurrent/refractory Hodgkin lymphoma. This combination requires monitoring for pulmonary toxicity, but can be used as a bridge to more definitive treatment.